The Relationship Between Employee Training, Career Development, and Job Satisfaction: A Case Study of Medium Scale Enterprise in Bandung City - Rijal, Syamsu; Sesario, Revi (IJBLE Scientific Publications Community Inc., 2024)
This study examines the relationships between employee training, career development, and job satisfaction within medium-scale enterprises in Bandung City. Utilizing a quantitative approach, data were collected from 200 employees through structured questionnaires. Descriptive statistics, reliability and validity assessments, normality and multicollinearity tests, and Pearson correlation analysis were conducted using SPSS software. The findings reveal that employee training and career development are significantly positively correlated with job satisfaction. Specifically, career development shows the strongest correlation with job satisfaction, followed by employee training. These results underscore the importance of investing in comprehensive training programs and robust career development initiatives to enhance job satisfaction. The study's implications for practice suggest that medium-scale enterprises should strategically focus on employee development to foster a more motivated and satisfied workforce, ultimately contributing to organizational success. Future research should explore these relationships longitudinally and in diverse organizational contexts.